Struktur Asam Nukleat dan Analisis Mutasi Gen terhadap Pembentukan Sel Kanker - Alisya Nur Aulia Ketaren; Aulia May Dinda; Airyn Dwi Rezkiqa; Rahma Azizah Harahap; Nur Hasanah; Zakia Rahma; Ida Duma Riris (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Nucleic acids are extremely important biomolecules. Their function is to store, regulate, and pass on genetic information in living organisms. There are two main types of nucleic acids: DNA (deoxyribonucleic acid) and RNA (ribonucleic acid), which are composed of small units called nucleotides. This study aims to explain the structure and function of DNA and RNA, as well as to distinguish their characteristics. Additionally, this study analyzes the relationship between gene mutations and the formation of cancer cells. The method used is a literature review employing a qualitative descriptive approach, conducted by examining various scientific journals from both domestic and international sources. The results of the study indicate that DNA has a double-helix structure that functions to store genetic information stably, while RNA is typically a single strand that plays a role in protein synthesis. Genetic changes caused by DNA damage can alter the sequence of nitrogenous bases, which has the potential to lead to the growth of cancer cells. Analysis using graph decomposition indicates that deletion and insertion mutations have a greater impact on genetic structural changes compared to substitution mutations. Additionally, natural substances rich in antioxidants, such as turmeric, green tea, garlic, and soursop leaves, can help prevent DNA damage. Thus, understanding the structure of nucleic acids and gene mutations is crucial for the advancement of genetics, molecular biology, and health technology.